Precision radiotherapy using MR-linac for pancreatic neuroendocrine tumors in MEN1 patients (PRIME): a protocol for a phase I-II trial, and systematic review on available evidence for radiotherapy of pNETs - van Vliembergen, Eline N. M.; Eijkelenkamp, Hidde; Valk, Gerlof D.; Vriens, Menno R.; Meijer, Gert J.; Intven, Martijn P. W.; de Laat, Joanne M. (Frontiers in Endocrinology, 2023)
Background: Surgical resection is the standard of care for the treatment of pancreatic neuro-endocrine tumors (pNETs) in patients with Multiple Endocrine Neoplasia Type 1 (MEN1). However, surgery can cause significant short- and long-term morbidity. Magnetic resonance-guided radiotherapy (MRgRT) is a potential effective treatment with little side effects. With traditional radiotherapy techniques, irradiation of pancreatic tumors to high dose levels was hampered by poor visibility of the tumor during treatment. MRgRT uses onboard MRI to guide the treatment, thereby enabling delivery of ablative irradiation doses to the tumor, while sparing surrounding tissues. In this study, we describe results from a systematic review assessing efficacy of radiotherapy in pNET and present the protocol of the PRIME study. Methods: PubMed, Embase and Cochrane Library were searched for articles assessing efficacy and side effects of radiotherapy for the treatment of pNETs. Risk of bias was assessed using the ROBINS-I Risk of Bias Tool for observational studies. Descriptive statistics were used to describe results of included trials. Results: Four studies comprising of 33 patients treated by conventional radiotherapy were included. Despite the heterogeneity of studies, radiotherapy appeared to be effective for the treatment of pNETs with most patients responding (45.5%) or stabilizing (42.4%) in tumor size. Conclusion and trial design: Due to the limited literature available and concerns about damage to surrounding tissue, conventional radiotherapy is currently little used for pNETs. The PRIME study is a phase I-II trial with a single arm prospective cohort study design, investigating the efficacy of MRgRT in MEN1 patients with pNET. MEN1 patients with growing pNETs with a size between 1.0 and 3.0 cm without malignant features are eligible for inclusion. Patients are treated with 40 Gy in 5 fractions on the pNET, using online adaptive MRgRT on a 1.5T MR-linac. The primary endpoint is the change in tumor size at MRI 12 months follow-up. Secondary endpoints include radiotoxicity, quality of life, endocrine and exocrine pancreas function, resection rate, metastatic free and overall survival. When MRgRT is found effective with low radiotoxicity, it could reduce the need for surgery for pNET and preserve quality of life.